The Effect of Songs in Teaching English Vocabulary at The Seventh Grade of SMPN 1 Labuapi - Rahayu, Mita; Kamaludin, Kamaludin; Azis, Atri Dewi; Lestari, Yuni Budi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research investigates the impact of using songs on English vocabulary acquisition among seventh-grade students at SMPN 1 Labuapi. It explores how songs can enhance vocabulary learning, boost student engagement, and create a more enjoyable learning environment. A quasi-experimental design was used, comprising a control group and an experimental group. Pre-tests and post-tests assessed vocabulary improvements. Results indicate that the experimental group demonstrated greater advancements in vocabulary mastery than the control group, highlighting the effectiveness of songs in language education.